Feline Injection Site Sarcomas: Data from Switzerland 2009–2014. (August 2018) - Graf, R.; Guscetti, F.; Welle, M.; Meier, D.; Pospischil, A.
Summary: Feline injection site sarcomas (FISS) were first described in the early 1990s. Despite extensive research, the pathogenesis of these tumours has not been elucidated conclusively. Their appearance and the marked increase in their incidence has been mainly connected to the injection of vaccines, and it is assumed that a chronic inflammatory reaction at the injection site triggers subsequent malignant transformation. The role of alum-based adjuvants has been discussed, but is controversial. The present study of the Swiss Feline Cancer Registry (SFCR) with data from 2009 to 2014 revealed a marked decrease of the incidence of fibrosarcomas compared with the previous observation period. Notably, this drop occurred after a non-adjuvanted feline leukaemia virus vaccine was introduced in Switzerland in 2007. This observation, together with the previous findings of the SFCR, further supports the notion that alum-adjuvanted vaccines are involved in the genesis of FISS and that non-adjuvanted vaccines might be safer for cats.